2002
DOI: 10.1051/parasite/2002093207
|View full text |Cite
|
Sign up to set email alerts
|

Monogeneans from Pangasiidae (Siluriformes) in Southeast Asia: III. Five new species ofThaparocleidusJain, 1952 (Ancylodiscoididae) fromPangasius bocourti,P. djambalandP. hypophthalmus

Abstract: M o n o g e n e a n s f r o m Pa n g a s iid a e (Siluriformes) in S outheastThe examination of gill parasites from Pangasius bocourti Sauvage, 1880; P. djambal Bleeker, 1846; P. hypophthalmus (Sauvage, 1878) and P. gigas Chevey, 1 9 3 0 (Siluriformes, Pangasiidae) revealed the presence of seven species of Monogenea among which five are considered new species. They all belong to Thaparocleidus Jain, 1952 (Ancylodiscoididae) as defined by Lim (1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…After dissection, their left gill arches were preserved in 70% ethanol. Species identification was based on the morphology of sclerotized parts of the attachment and reproductive organs following Lim [32] and Pariselle et al [28, 3336]. All Thaparocleidus species collected for this study were found on a single host species except for T. caecus , which was collected from Pangasius nasutus and Pangasianodon hypophthalmus (this host species has been introduced over the entire region of Southeast Asia for aquaculture purposes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After dissection, their left gill arches were preserved in 70% ethanol. Species identification was based on the morphology of sclerotized parts of the attachment and reproductive organs following Lim [32] and Pariselle et al [28, 3336]. All Thaparocleidus species collected for this study were found on a single host species except for T. caecus , which was collected from Pangasius nasutus and Pangasianodon hypophthalmus (this host species has been introduced over the entire region of Southeast Asia for aquaculture purposes).…”
Section: Methodsmentioning
confidence: 99%
“…All Thaparocleidus species collected for this study were found on a single host species except for T. caecus , which was collected from Pangasius nasutus and Pangasianodon hypophthalmus (this host species has been introduced over the entire region of Southeast Asia for aquaculture purposes). However, host specificity in this study (Table 1) was evaluated at global level; that is, the data on host range of each analyzed Thaparocleidus species were retrieved from published studies [28, 3337]. Thus, parasite species were separated into two categories: specialist parasitizing a single host species and generalist parasitizing at least two different host species [38].…”
Section: Methodsmentioning
confidence: 99%
“…Lerssutthichawal et al (1999) recorded T. caecus from three host fishes: Pangasius conchophilus, Pangasius larnaudii and P. hypophthalmus, and T. siamensis from P. hypophthalmus cultured in Thailand. Pariselle et al (2002) recorded T. caecus from both P. hypophthalmus and Pangasius djambal and T. siamensis Lim 1996). The copulatory organ, as illustrated by Rastogi et al (2008), in particular, is not even close to that of T. vistulensis.…”
Section: Resultsmentioning
confidence: 81%
“…Evidently, T. caecus is a generalist parasite with wide host specificity, and thus most likely to represent a natural threat to native fish biodiversity of importing countries. Pariselle et al (2002) Considering continuing worldwide introductions/exports of P. hypophthalmus for aquarium and/or aquaculture purposes, we anticipate further range expansion for these parasites. It seems only relevant and essential that parasitologists consider the potential impact of parasites onto the economically important P. hypophthalmus farming.…”
Section: Disease Risk Implicationsmentioning
confidence: 99%